2020
DOI: 10.1093/arclin/acaa070
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Pediatric Teleneuropsychology: A validation study

Abstract: Objective To evaluate home-based teleneuropsychology in a pediatric cohort to determine if assessment via in-person and home-based videoconference yield similar results. The second objective was to determine the level of satisfaction with videoconference-based assessment among participants and caregivers. Method Fifty-eight participants, aged 6–20 years, were recruited through specialty programs for pediatric demyelinating di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 12 publications
4
102
0
Order By: Relevance
“…Anecdotally, many providers have stressed concern for the technical difficulties that may arise during a TeleNP evaluation. Consistent with findings in the adult TeleNP literature and Harder and coworkers (2020) , our results demonstrated a limited frequency of interruptions related to technical difficulties, comparable to typical interferences that may occur during an-person evaluation (e.g., noise control outside of the testing room, etc.). To minimize technological interruptions, providers should ensure that they are using a reliable platform and that patients are instructed in reliable network connectivity in advance.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Anecdotally, many providers have stressed concern for the technical difficulties that may arise during a TeleNP evaluation. Consistent with findings in the adult TeleNP literature and Harder and coworkers (2020) , our results demonstrated a limited frequency of interruptions related to technical difficulties, comparable to typical interferences that may occur during an-person evaluation (e.g., noise control outside of the testing room, etc.). To minimize technological interruptions, providers should ensure that they are using a reliable platform and that patients are instructed in reliable network connectivity in advance.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we were unable to replicate findings in the adult TeleNP literature demonstrating similar test results across remote and face-to-face assessment conditions. However, Harder and coworkers (2020) have recently validated home-based TeleNP in a pediatric sample. Further investigation of pediatric TeleNP is needed to replicate these findings, expand the sample size, population diversity, and measures used with pediatric subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With technological advances, clinicians are now afforded an opportunity to provide neuropsychological services using telemedicine. Harder and colleagues shared the first pediatric study that indicated that home-based neuropsychological services may be valid, feasible, and acceptable for specific clinical populations with limitations due to medical conditions ( Harder et al., 2020 ). The importance of recognizing the breadth of clinical services neuropsychologists can offer patients has increased during the COVID-19 pandemic given the physical distancing constraints for in-person clinical neuropsychological evaluations ( Bilder et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%